Is Mesh Becoming More Popular? Dilemmas in Urogynecology: A National Survey. (15th November 2011) - Condrea, Alexander; Netzer, Itamar; Ginath, Shimon; Eldor-Itskovitz, Joseph; Golan, Abraham; Lowenstein, Lior
Abstract : The use of vaginal mesh in pelvic organ prolapse (POP) repair surgery has become more common in recent years. The purpose of the current study was to evaluate the common practice of Israeli urogynecologists, and to determine whether surgical practice has changed over the last two years. Methods . In 2009 and again in 2011, a survey was mailed to all urogynecologists affiliated with an academic institute in Israel. The survey consisted of 7 Likert-scale items and 3 open questions; the latter inquired about preferred type of surgery in three clinical scenarios. Results . Of 22 practitioners, 15 responded to the survey. The number of urogynecologists who reported using vaginal mesh for the repair of primary POP increased from 47 to 67% from 2009 to 2011. The number who would not use vaginal mesh in POP repair of elderly patients dropped from 60 to 3%. Finally, for the treatment of a 35-year-old patient with stage III uterine prolapse who desired to preserve fertility, 13% recommended the used vaginal mesh in 2009 compared with 47% in 2011. Conclusion . A survey of practitioners shows that the use of vaginal mesh for the repair of primary and recurrent pelvic organ prolapse has become more common among Israeli urogynecologists.